Digital Analysis of Nasal Airflow Facilitating Decision Support in Rhinosurgery - Hildebrandt, Thomas; Brüning, Jan Joris; Lamecker, Hans; Zachow, Stefan; Heppt, Werner J.; Schmidt, Nora; Goubergrits, Leonid (Facial Plastic Surgery, 2019)
Successful functional surgery on the nasal framework requires reliable and comprehensive diagnosis. In this regard, the authors introduce a new methodology: Digital Analysis of Nasal Airflow (diANA). It is based on computational fluid dynamics, a statistical shape model of the healthy nasal cavity and rhinologic expertise. diANA necessitates an anonymized tomographic dataset of the paranasal sinuses including the complete nasal cavity and, when available, clinical information. The principle of diANA is to compare the morphology and the respective airflow of an individual nose with those of a reference. This enables morphometric aberrations and consecutive flow field anomalies to localize and quantify within a patient’s nasal cavity. Finally, an elaborated expert opinion with instructive visualizations is provided. Using diANA might support surgeons in decision-making, avoiding unnecessary surgery, gaining more precision, and target-orientation for indicated operations.
Keywords: nasal airflow simulation; nasal breathing; statistical shape model; diANA; nasal obstruction; rhinorespiratory homeostasis